Kings, politics, and the right order of the world in German historiography c. 950-1150 - Bagge, Sverre, 1942- (Studies in the history of Christian thought, 2002)
A discussion of German historiography from around 950 to 1150, through a close examination of six works. It focuses on the narrative as an expression of the author's way of finding meaning in the sequence of events, and as evidence for their understanding of society, politics and human behaviour.